2003
DOI: 10.1377/hlthaff.22.2.219
|View full text |Cite
|
Sign up to set email alerts
|

The Rise Of Nursing Home Litigation: Findings From A National Survey Of Attorneys

Abstract: Lawsuits against nursing homes are a relatively recent phenomenon. Despite a growing sense of alarm among policymakers, little is known about these lawsuits' scale, dynamics, or outcomes. To describe these characteristics, we conducted a Web-based survey of attorneys nationwide who bring and defend this litigation. Our respondents and their firms were involved in 4,677 and 8,256 claims, respectively, in 2001; more than half of these claims were in Florida and Texas. The costs of nursing home litigation are sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 5 publications
0
37
0
Order By: Relevance
“…Most studies argue that ‘an uneasiness with discussion and reporting of errors’ in nursing homes in the USA is an important cause of the poor PSC 9 13. This uneasiness and the related policies and processes may be a reaction of US nursing home management to the tremendous rising costs of litigation because of the increasing number and severity of lawsuits connected to patient safety in nursing homes 26. Such a legal claim culture is absent in the Dutch healthcare system.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies argue that ‘an uneasiness with discussion and reporting of errors’ in nursing homes in the USA is an important cause of the poor PSC 9 13. This uneasiness and the related policies and processes may be a reaction of US nursing home management to the tremendous rising costs of litigation because of the increasing number and severity of lawsuits connected to patient safety in nursing homes 26. Such a legal claim culture is absent in the Dutch healthcare system.…”
Section: Discussionmentioning
confidence: 99%
“…A recent national study showed that only 17% of nursing homes reported special program trained staff for palliative/end-of-life care, and only 19% reported such staff training for hospice care 38 . Furthermore, it appears that law suits against nursing homes, largely by residents’ family members, represent the fastest growing area of healthcare litigations 39 . Perhaps as a result, nursing home physicians and facilities concerned with liability issues 31 may have become increasingly more inclined to hospitalize residents at the end-of-life, thus increasing the likelihood of inhospital death.…”
Section: Discussionmentioning
confidence: 99%
“…If particularly ill patients refuse hospitalization, mortality may increase. Providing care to more acutely ill patients in nursing homes ill prepared to do so may take time away from other residents, increasing the potential for adverse events and litigation (Stevenson and Studdert 2003). Absence of a bed-hold policy may prolong hospitalization due to difficulty in determining a locale for hospital discharge (Nohlgren 2004).…”
Section: Discussionmentioning
confidence: 99%